2021
DOI: 10.1051/matecconf/202133601004
|View full text |Cite
|
Sign up to set email alerts
|

Sound source location for low-altitude aircraft based on sub-band extraction

Abstract: The acoustic signal of low-altitude aircraft shows regular distribution in frequency and has obvious harmonic crest of both fundamental frequency and double frequency.Therefore, this paper presents a low complexity algorithm of acoustic location based on feature sub-band extraction for low-altitude aircraft. The algorithm firstly searches the eigenfrequency points which occupy the main energy in the sound signal. Then the cost function is constructed based on the MUSIC method by the sub-band corresponding to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…The authors assert that this approach demonstrated a notable enhancement compared to the state-of-the-art TDOA-based algorithm. In [ 132 ], the authors presented an extension of the MUSIC algorithm incorporating sub-band extraction. This extension involves identifying sub-bands associated with characteristic frequency points and subsequently conducting Direction of Arrival estimation.…”
Section: Acoustic Source Detection and Localization Applicationsmentioning
confidence: 99%
“…The authors assert that this approach demonstrated a notable enhancement compared to the state-of-the-art TDOA-based algorithm. In [ 132 ], the authors presented an extension of the MUSIC algorithm incorporating sub-band extraction. This extension involves identifying sub-bands associated with characteristic frequency points and subsequently conducting Direction of Arrival estimation.…”
Section: Acoustic Source Detection and Localization Applicationsmentioning
confidence: 99%